Corporate Governance of State-Owned Enterprises in Europe and Central Asia : A Survey - World Bank (World Bank, Washington, DC, 2021)
The Corporate Governance of State-Owned Enterprises in Europe and Central Asia Survey analyzes the transparency and control environment governing state-owned enterprises (SOEs) in selected countries of the Europe and Central Asia Region (ECA), with an emphasis on financial reporting, auditing, and transparency requirements. The survey builds on and complements several studies on SOE governance that World Bank teams have carried out around the ECA Region. The purpose of this survey is to provide the countries with an easy-to-follow benchmarking comparison of SOE practices in accountability requirements across the ECA Region. The survey will also inform ongoing and future World Bank assistance to partner countries in the areas of SOE financial accountability, controls, and transparency. The survey aims to assist governments and SOE ownership entities in carrying out reforms and implementing effective SOE monitoring mechanisms and corporate governance practices.